Olfactory-Mediated Fear Conditioning in Mice: Simultaneous Measurements of Fear-Potentiated Startle and Freezing - Jones, Seth V. (2005)
This study demonstrates that mice display olfactory-cued fear as measured with both freezing and fear-potentiated startle. Following a preconditioning test to measure any unconditioned responses to odor, mice received 5 pairings of a 10-s odor with a 0.25-s, 0.4-mA footshock. The next day, startle and freezing were measured in the presence and absence of the odor. Both fear measures increased after training with amyl acetate (Experiment 1) and acetophenone (Experiment 2). The enhancement of startle did not occur when the same number of odors and shocks were presented in an unpaired fashion (Experiment 3). Furthermore, mice were able to discriminate between an odor paired with shock and a nonreinforced odor (Experiment 4).